Novel insights into neuron-glia communication: the case of neuroinflammation triggered by Maneb - Benzi Juncos, Oriana Nicole (2022)
INTRODUÇÃO: Maneb is a dithiocarbamate pesticide which prolonged use is considered an environmental risk factor for Parkinson’s disease (PD). An important component in PD pathogenesis is neuroinflammation. Chronic neuroinflammation is established when resolution process fails to limit pro-inflammatory stimulus, thus triggering neuronal death. Prostaglandins and resolvins are specialized and essential lipid mediators in the inflammation/resolution process. They are oxygenated derivatives of arachidonic (AA) and docosahexaenoic (DHA) acids that act as ligands for specific G-protein coupled receptors. OBJETIVOS: Our aim was to study the spatial-temporal production of inflammation/resolution signals and their specific role throughout Maneb-induced injury in neuronal and glial cells. For this purpose, molecular components of the inflammation/resolution cascade were studied in dopaminergic neurons, astrocytes and their secretomes challenged with the pesticide. MÉTODOS: N27 dopaminergic neuronal and C6 astrocyte cell lines were exposed to 20 µM Maneb or vehicle for 24 h in the presence of pharmacological inhibitors and antagonists of different components of the inflammation/resolution pathways. Cell viability and cellular oxidant levels were determined by MTT reduction and dichlorofluorescein assays, respectively. Cell proliferation was evaluated by Bromodeoxyuridine incorporation assay. After treatments, protein and gene expression was measured by Western blot, Immunocytochemistry and RT-qPCR. AA and DHA content was assessed by GC-MS. RESULTADOS: First, we characterized the redox status of neurons exposed to Maneb. We determined that the increase in reactive oxygen species triggered by the pesticide was associated with a downregulation of antioxidant defenses (hemeoxigenase-1, glutathione cysteine ligase and superoxide dismutase). The oxidative injury triggered by Maneb was accompanied by a different profile in AA and DHA content in neurons and astrocytes. Increased neuronal DHA levels were associated with exacerbated cell death observed in the presence of Maneb and the FPR2/ALX antagonist, QuinC7. Astrocyte-derived secretome was able to prevent Maneb-triggered neuronal death and also to revert the deleterious effect of FPR2/ALX blockage. In line with this, astrocytes showed decreased AA and DHA levels, which were coincident with their secretome-mediated neuroprotective role. Pharmacological inhibition of key enzymes (cyclooxygenase-2, lipoxygenase-15, cytochrome P450) responsible for the production of inflammation/resolution related lipid mediators demonstrated that the spatial (neurons or astrocytes) activation of these pathways was involved in the cellular response to Maneb- induced toxicity. CONCLUSÕES: Our results point towards a neuroprotective role of astroglia through the orchestrated activation of resolution mechanisms against pesticide toxicity